Optics, Photonics and Laser Technology (Springer Series in Optical Sciences,, 2018)
This book covers both theoretical and practical aspects within optics, photonics and lasers. It deals with optical instrumentation and metrology, photonic and optoelectronic materials and devices, nanophotonics, organic and bio-photonics and high field phenomena. Researchers, engineers, students and practitioners interested in any of these fields find here new methods, technologies, advanced prototypes, systems, tools and techniques as well as general surveys indicating future directions. .